2012
DOI: 10.1111/j.1365-2605.2012.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic effect of bone marrow mesenchymal stem cells for erectile dysfunction in diabetic rats

Abstract: It has been demonstrated that intracavernous injection of bone marrow-derived mesenchymal stem cells (BM-MSCs) had beneficial effects on improving erectile function in type-1 diabetic rats. This study was designed to investigate the neurotrophic effect of BM-MSCs for type-1 diabetic rats. Streptozocin-induced type-1 diabetic rats were randomly divided into three groups: diabetic group, BM-MSCs-treated group and BM-MSCs-conditioned medium-treated group. At the 3d, 1 and 2w time points after BM-MSCs injection, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 31 publications
1
48
0
1
Order By: Relevance
“…These results are consistent with previous findings about diabetic rats. 10,24 ADSCs are adult stem cells with multipotency and low immunogenicity. 22 Moreover, they have been applied to repair muscle tissues and restore tissue vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous findings about diabetic rats. 10,24 ADSCs are adult stem cells with multipotency and low immunogenicity. 22 Moreover, they have been applied to repair muscle tissues and restore tissue vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their antiapoptotic effect within the corpora, Sun et al subsequently showed that BM-MSCs are capable of promoting neuroregeneration through the secretion of neurotrophins, specifically brainederived neurotrophic factor (BDNF), nerve growth factor (NGF), and vascular endothelial growth factor (VEGF). 19 …”
Section: Bone Marrowederived Mesenchymal Stem Cellsmentioning
confidence: 97%
“…Various studies demonstrated that stem cells secrete many growth factors, including CXCL5, adrenomedullin, bFGF, VEGF, nerve growth factor and BDNF [19,[34][35][36]. These growth factors exhibit potent angiogenic and neurotrophic activities.…”
Section: Discussionmentioning
confidence: 99%